Perinatal influences on academic achievement and the developing brain: a scoping systematic review - Schneider, Deborah; Bouhali, Florence; Richter, Caroline G.; Costache, Radu; Costache, Catalina; Kirchhoffer, Kaitlyn; Sheth, Vatsa; MacDonald, Ibo; Hoeft, Fumiko (Frontiers in Psychology, 2024)
In this PRISMA compliant systematic review, we identify and synthesize the findings of research in which neuroimaging and assessments of achievement have been used to examine the relationships among aspects of developmental programming, neurodevelopment, and achievement in reading and mathematics. Results: 46 studies met inclusion criteria. The majority examined the impact of prematurity (n=31) and prenatal alcohol exposure (n=13). Several prematurity studies reported a positive correlation between whitematter integrity of callosal fibers and executive functioning and/or achievement, and white matter properties were consistently associated with cognitive and academic performance in preterm and full-term children. Volumetric studies reported positive associations between academic and cognitive abilities and white and grey matter volume in regions such as the insula, putamen, and prefrontal lobes. Functional MRI studies demonstrated increased right-hemispheric language processing among preterm children. Altered activation of the frontoparietal network related to numerical abilities was also reported. Prenatal alcohol exposure studies reported alterations in white matter microstructure linked to deficits in cognitive functioning and academic achievement, including mathematics, reading, and vocabulary skills. Volumetric studies reported reductions in cerebral, cerebellar, and subcortical gray matter volumes associated with decreased scores on measures of executive functioning, attention, working memory, and academic performance. Functional MRI studies demonstrated broad, diffused activation, reduced activation in canonical regions, and increased activation in non-canonical regions during numeric tasks. Discussion: A preponderance of studies link prematurity and prenatal alcohol exposure to altered neurodevelopmental processes and suboptimal academic achievement. Limitations and recommendations for future research are discussed.